Fabrication of theranostic amphiphilic conjugated bottlebrush copolymers with alternating heterografts for cell imaging and anticancer drug delivery. Issue 39 (6th September 2018) - Liu, Fangjun; Zhao, Xuezhi; Zhang, Xiaolong; Zhang, Xianshuo; Peng, Jinlei; Yang, Huiru; Deng, Kaicheng; Ma, Liwei; Chang, Cong; Wei, Hua
Abstract : We reported the first example of polyfluorene (PF)-backboned bottlebrush ( bb ) copolymers with alternating POEGMA/PCL hetero brushes for cancer theranostics. Abstract : Bottlebrush ( bb ) copolymers with hetero-polymer grafts represent an intriguing advanced macromolecular architecture due to the unique phase-separation of the pendant side chains for polymer self-assembly and various functionalizations. However, compared to the well-developed polyfluorene (PF)-backboned bb copolymers with homobrushes, the incorporation of heterobrushes remains unexplored likely due to the synthetic challenges. For this purpose, we reported in this study the synthesis of a series of well-defined amphiphilic conjugated bb copolymers, PF-(( g -PCL-OOCCH3 )- alt -( g -POEGMA)) with alternating poly(oligo(ethylene glycol)monomethyl ether methacrylate) (POEGMA)/poly(ε-caprolactone) (PCL) grafts, by integrated state-of-the-art polymer chemistry techniques including Suzuki-coupling polycondensation, ring-opening polymerization (ROP), click reaction and atom transfer radical polymerization (ATRP). One identified polymer construct (P4 ) was able to form stabilized unimolecular micelles in an aqueous solution with a diameter of approximately 68 nm and showed the highest fluorescence quantum yield of 0.55, which is on a par with that of the small organic molecular fluorophore standard, quinine sulfate. The potential of P4 for simultaneous cell imaging and drug delivery was further evaluated in vitro, which confirmed efficient cellular uptake and cytotoxicity in HeLa cells. This study thus presents the first example of PF-backboned bb copolymers with alternating heterobrushes for cancer theranostics.